The Role of the Entrepreneur in Driving Innovation in The Window Industry: from Traditional Structures to High-Tech Solutions - Kovalskyi, Serhii (Global Prosperity, 2026)
The current research explores the entrepreneur as a key factor for innovation in the window industry, an industry that is undergoing a significant transformation due to smart innovations, energy efficiency requirements, and digitalization. Although the development of technologies, ranging from electrochromic glazing, thermochromic materials to smart window systems, has greatly developed the landscape of technological innovation, their uptake is uneven and especially among small and medium-sized enterprises (SMEs). From this perspective, we conclude these studies that window innovation depends not solely on technological availability but that entrepreneurial orientation, digital transformation, and organizational alignment are also essential for the innovation process to succeed in the window sector. The study builds on an empirical review of extant literature, proposing the Entrepreneurial Innovation Driver Model (EIDM) which is a framework that defines innovation as an interaction of three salient dimensions: entrepreneurial orientation, digital transformation capabilities, and technological adoption. The results suggest the role of the entrepreneur as a strategic integrator of mission-critical functions of strategic vision, operational functioning, and technological implementation. A major innovation gap identified by the study is between the potential of technologies and their actual application, which is largely the result of managerial and organizational barriers. In addition, the paper builds upon the preceding literature by providing a process-oriented framework for the exploration of innovation in the window industry while providing practical insights to SMEs who want to shift towards hi-tech, energy-efficient solutions.